FDG–PET CT in the evaluation of primary and secondary pancreatic malignancies. Issue 10 (11th May 2018) - Bohl, Casey E.; Federico, Sara M.; Robinson, Giles W.; Bahrami, Armita; Shulkin, Barry L.
Abstract: Purpose: Primary pancreatic carcinoma and pancreatic metastases are rare in the pediatric population. Pancreatoblastoma is the most common pancreatic malignant tumor in young children and solid‐pseudopapillary tumor in teenagers. Pancreatic adenocarcinoma is extremely rare under the age of 40 and is usually associated with underlying genetic abnormalities. Secondary malignancies of the pancreas occur more frequently than primary pancreatic malignancies in children and are most commonly seen with non‐Hodgkin lymphomas (NHL) and mesenchymal sarcomas. The purpose of this study was to characterize the metabolism of primary and secondary tumors of the pancreas in pediatric patients. Materials and methods: A retrospective analysis of all primary and secondary pancreatic malignancies imaged with 18F‐fluorodeoxyglucose (FDG)–positron emission tomography (PET) computed tomography (CT) was conducted. Results: Three patients with primary pancreatic cancers were identified, one each with pancreatoblastoma, solid‐pseudopapillary tumor, and adenocarcinoma. Each tumor showed elevated uptake of FDG. Metastatic disease in the pancreas was identified in 12 patients—five NHL (including three Burkitt lymphomas), six sarcomas (three osteosarcomas, two rhabdomyosarcomas, and one Ewing sarcoma family tumor), and one malignant rhabdoid tumor. Elevated but variable uptake of FDG was found in each of the tumors of patients with metastatic disease within the pancreas. Conclusion: Both primary malignancies and metastatic disease within the pancreas, though very rare in children, adolescents, and young adults, are metabolically active and can be functionally characterized using FDG–PET CT.